The Effect of Corruption and Political Instability on Firm’s Performance: Evidence from Low Income Economies - Kazmi, Syed Mumtaz Ali Kazmi; Imran, Syed Muhammad; Farooqi, Khalid Farooq; Shahid, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2022)
Low-income economies have characteristics of high corruption and political instability. The underdeveloped corrupt financial system of low-income nations with political instability may constrain firms’ performance. The objective of the current study was to estimate the effect of corruption and political instability on firms’ performance in low-income economies. The recent study used firm investment in human capital and exports as a proxy to measure the firm’s performance. We have applied logistic regression to the World Enterprise Survey dataset to find the probability of firms’ investment in human capital. The study concluded that corruption and political instability decrease the likelihood of a firm’s human investment in human capital. Firm-specific characteristics increase the probability of firms’ exports. For policy purposes, corruption must be reduced to increase firms’ investment in human capital.